Being a dog : a tail of mindfulness [book with audioplayer] - Gianferrari, Maria ([Library Ideas, LLC], 2022)
Join a young child and their dog as they experience every minute of the day to its fullest from the second they wake up to the moment they fall asleep. Readers will love barking, wagging, and sniffing along with the gentle cues in the book.